Estudio de factibilidad para el desarrollo de un sistema de gestión compra y venta de los productos farmacéuticos en la Farmacia Junior ubicado en el Recinto Pueblo Nuevo de la Parroquia Febres Cordero - Herrera Vasquez, Bryan Steeven (2021)
The present investigation is a feasibility study for the development of a management system purchase and sale of the pharmaceutical products in the Junior pharmacy located in the recinto Pueblo Nuevo of the Febres Cordero Parish, is for improve the process within the Junior pharmacy in the entry and exit of the pharmaceutical products and thus be able to reduce the response time in the purchases and sales of said products. In the viability of the case study, the objective is to determine the various factors that exist when analyzing the possible risks, show the influence on the development of the system, but the results obtained in the research will also be evaluated through the feasibilities, methodologies, techniques and instruments, considering the great importance of the company to generate the most convenient strategy in the process that is carried out in the purchase and sale of pharmaceutical products. It allows to avoid monetary losses for the company because this system entails greater efficiency both in the acquisitions and in the distribution of the products demanded by the clients.